Looped Distribution System Radialization Algorithm for Power Flow Analysis Including DC Line and Sectionalizing Switch - Widiputra, Victor; Yun, Sangwon; Jung, Jaesung (Journal of Electrical Engineering and Technology, 2019)
This paper proposes the incorporation of a DC line and loop system into the power flow study of a distribution system. A Modified Backward Forward Sweep (BFS) algorithm based on the sequential method is utilized to solve the power flow problem in a power system containing loop caused by either a DC line or a sectionalizing switch. It solves the power flow problem by treating the DC line or sectionalizing switch as two unconnected nodes, thus changing the system into a radial one. Their equivalent parameters are then found at the distribution system’s point of common coupling (PCC) and are used in the radial power flow calculation. BFS is employed to calculate the power flow solution after the system becomes radial. Finally, convergence is achieved when the voltage difference at the PCC calculated from the current and previous iterations is below the tolerance level. Test cases are presented to verify the proposed algorithm, and results show that the proposed algorithm achieves an identical result to the reference values.
Keywords: DC line; Distribution systems; Forward sweeps; Loop power flow; Point of common coupling; Backward forward sweep (BFS); DC line; Distribution system; Loop power flow; Point of common coupling (PCC)